APOPTOSIS INDUCTION HUMAN TONGUE CANCER CELLS Supri's clone - 1 (SP-Cl) USING DIFFERENT CONCENTRATION ETHANOL EXTRACT AT PUKUL EMPAT LEAF (Mirabilis Jalapa L.) - , Mierna Fatima ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
MirabilisJalapa L. known to contain proteins similar ribosome-inactivating protein (RIP)that can inhibit human cancer cells. The purpose of this study was to prove the potential of ethanol extract of pukul empat leaves (Mirabilis Jalapa L.) against the induction of apoptosis in cancer cells of the human tongue SP-Cl. The design of this study is purely experimental laboratory. Cancer cells supri's-clone 1 (SP-Cl) were bred in mikroplate 24 well containing a cover slip coupled with media Dulbecco's Modified Eagle Medium (DMEM) was then added to each concentration (0, 7.5, 15,25, 50, 75J.&mu